PERANCANGAN DAN ANALISA JARINGAN KOMPUTER DENGAN MENGGUNAKAN TEKNOLOGI NIRKABEL BERBASIS WIFI PADA STMIK AMIKOM PURWOKERTO - Muhammad Imron (Universitas Amikom Purwokerto, 2010)
The purpose of this research is to design a computer network-based wireless technolgy with Wi-Fi, especially to overcome problems that occur due to design of computer network are still based on cable technology that is still widely used and inefficient use of bandwidth for file transfer. The methods used include two main parts namely the design methods amd analytical methods. Design method is used to create a wireless network topology as well as making new applications for file transfer and analytical methods used to analyze system that are running. So that the results achieved is the design of a network that has high mobility and bandwidth savings. Conclusions obtained that by conversion system from Ethernet networks into wireless network to increase the number of clients that can access into the network and could increase employee mobility notebook users. In addition, the addition of a new file transfer application could reduce traffic to the Internet bandwidth usage. Keywords : wirelless LAN, access point, Wi-Fi topology, File Transfer.